C2C: um chat bilíngue com apoio de senso comum - Sugiyama, Bruno Akio (2011)
In this research, we describe how common sense knowledge with machine translation can help the communication among people with different cultural background. In order to evaluate this possibility, we developed a bilingual chat called Culture-to-Chat or C2C that provides a communication channel and has resources that help its user to create messages in a second language. In the computer-mediated communication field, it is possible to notice that people are crossing geographic borders and having opportunities to share experiences among different cultures. Sharing information in a non native language can be difficult to some users. Some computational tools that support communication uses machine translation to aid users that need to work with different language. C2C also uses this approach and adopts a semantic network of cultural knowledge, collaboratively built on the Web through the Open Mind Common Sense in Brazil project (OMCS-Br) to work with cultural expression, in other words, terms whose meaning depends on user‟s culture. Following a user-centered design approach that focuses on prototyping, we present the development of C2C passing by low, middle and high fidelity prototypes. In order to observe how this computational tool is used and collect the opinion of target users, we perform a pilot study involving Brazilian and Canadian users. This study showed some enhancements for the tool and pointed evidences that this chat contributes to the communication between people with different cultural backgrounds.